Teachers Perceptions about the Importance of English for Young Learners - Ayu Oktaviani; Asahi Fauzan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The objective of the research was to find out teachers perceptions about the importance of English for young learners at Elementary Schools in Lubuklinggau Timur I . The sample of the research was 83 teachers from 4 Elementary Schools in Lubuklinggau Timur I. The samples were taken through cluster random sampling. The researcher used survey research and the data were collected by using questionnaire and interview. Technique for analyzing the data used simple basic statistical technique. The data were scored by using Likert scale. The results of the research were 1 If the young learners learn English early, the English mastery will be better, 2 English will be useful for the young learners to get a job in the future, and 3 By mastering English, the young learners will have the social and economic benefits in the future. Therefore, it can be concluded that the teachers of Elementary Schools in Lubuklinggau Timur I agreed that English for Young Learners was important. Key word: teachers perceptions, importance of English, young learners